PENGARUH PELAYANAN PERANGKAT DESA, TRANSPARANSI PENGGUNAAN DANA DESA, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN DESA LUWUNGRAGI - Safira Utami; Dumadi Dumadi; Yenny Ernitawati (Jurnal Bina Bangsa Ekonomika, 2024)
Tax compliance is defined as when a taxpayer fulfills all tax obligations and exercises his or her tax rights. This study aims to find empirical evidence about the factors that affect the compliance of land and development taxpayers. The factors tested in this study are village apparatus services, transparency of village funds, and taxpayer awareness. The population of this study is all taxpayers of Luwungragi Village, Brebes Regency. This sample was selected by a non-probability technique. The number of samples from this study is 97 taxpayers. The data analysis used is a data quality test which includes validity and reliability testing, a classical assumption test which includes a normality test, multicollinearity, heteroscedasticity, and autocorrelation test. The hypothesis test uses multiple linear regression techniques, persial significance test (t-test), simultaneous test (F test) and determination coefficient (R2). The results of the study stated that partially village apparatus services have a significant positive effect on taxpayer compliance, transparency in the use of village funds has a significant positive effect on taxpayer compliance, taxpayer awareness has a significant positive effect on taxpayer compliance, and simultaneously village apparatus services, transparency in the use of village funds, and taxpayer awareness have a significant effect on taxpayer compliance